Specify some heavy metals in select wellsWater at Basrah,Iraq - . Mahmood, Amal; . Mahmood, Amal (University of Thi-Qar Journal of Science, 2015)
The present study was undertaken to determine the means of some heavy metals in randomly choosen wells fromBasrah: tow regions before raining period during October 2011 (Bergussia and Zubair) and three regions (Bergussia , Zubair and Marbed) after raining period during July 2012. The concentrations of heavy metals Cd, Cr, Cu, Fe, Ni, Mn, Pb and Zn were 0.004, 0.37, 1.65, 5.25, 0.1, 0.4, 0.86, and 0.61mg/l respectively for the period before rain while 0.02, 1.37, 0.1, 0.01, 0.04, 0.0002, 0.01 and 1.15 mg/l respectively for the period after rain in Zubair and 0, 0.74, 1.49, 4.51, 0.09, 0.43, 0.51, 0.98 mg/l respectively for the period before rain while 0.03, 1.52, 0.11, 0.01, 0.01, 0.06,0.0002, 0.01and 1.20mg/l respectively in Bergussia, the concentrations recorded in Marbed were 0.8, 1.03, 0.13, 1.01,0.6, 0.001, 0, and 1.40mg/l respectively.The result showed significant deferences between the sites, and no segnifincat between wells and the rain was significant effect on concentration of heavy metals. Almost the reason the heterogeneity focus minerals Consequently, differences in the intensity of the on-site processes controlling thedistribution of major ions in melting and sedimentation to various metals. As well as the difference in controllingmain interaction during pumping operation during the process of pumping cause the differentiation in theconcentrations